Controller Concept for a Highly Parallel Machine Tool - HABERSOHN, Christoph; BLEICHER, Friedrich (Engineering Transactions, 2014)
Modern high performance cutting processes force high demands on new machine tool con- cepts with enhanced mechanical stability and better dynamic behavior. In the development of innovative machine tool concepts the main focus is still set on the design of mechanical struc- tures with parallel kinematics. The new machining center “X-Cut” consists of a double scissor kinematic structure with a degree of parallelism of two, incorporating four drives for the XY - plane movement. Thus, the arrangement of four interlinked axes leads to an over-determined kinematic structure. Due to the complex behavior of the kinematic structure a new method in NC-controller design and parameterization is needed, including enhanced compensation and preloading algorithms.